On-tissue derivatization for mass spectrometry imaging reveals the distribution of short chain fatty acids in murine digestive tract - Nakagawa, Kaoru; Okamoto, Mami; Nishida, Masako; Terashima, Kenta; Kobayashi, Manami; Teramoto, Kanae; Kubo, Akiko (Frontiers in Cellular and Infection Microbiology, 2025)
Short-chain fatty acids (SCFAs), which are produced by microorganisms in the digestive tract of animals, play an important role in maintaining homeostasis in the host, including immune function. Different types of SCFAs are produced by different intestinal bacterial communities. However, visualizing their spatial distribution within tissue sections has been difficult. This is primarily due to the volatility of SCFAs, which makes detection challenging, even with matrix-assisted laser desorption/ionization (MALDI) mass spectrometry imaging (MSI) using an atmospheric pressure ion source. To address this issue, we minimized the volatility of SCFAs in fresh tissue sections. Then, we used N,N,N-trimethyl-2-(piperazin-1-yl)ethan-1-amine iodide (TMPA) and 1-((dimethylamino)(dimethylimino)methyl)-1H- [1,2,3]triazolo[4,5-b]pyridine-3-oxide hexafluorophosphate (HATU) to chemically derivatize the carboxylic acid into a quaternary amine. This in situ derivatization enabled visualization of SCFAs using MALDI-MSI. In the cecum of mice, strong signals for butyrate and propionate were detected in areas with high bacterial density, as identified by hematoxylin staining. This indicates that these SCFAs are produced by bacteria. Anaerobic bacteria were cultured from the cecum of another individual raised under the same environment. Strain identification was performed using MALDI mass spectrometry of bacterial protein finger prints which confirmed the presence of bacteria that produce SCFAs. This approach, which combines minimizing volatility and in situ derivatization, provides a powerful tool for elucidating the spatial relationship between intestinal bacteria and metabolites including SCFAs.